EFEKTIFITAS PASTA GIGI HERBAL DAUN SIRIH DAN PASTA GIGI NON HERBAL DALAM MENGHAMBAT AKUMULASI PLAK (Politeknik Kesehatan Kemenkes Bandung, 2021)
Dental plaque is a soft deposit that is firmly attached to the tooth surface, consisting of microorganisms that multiply in an intercellular matrix if a person neglects dental and oral hygiene. Mechanical plaque control may include brushing and flossing. Toothpaste can be used as a supporting tool for plaque control. Toothpaste with herbal ingredients such as betel leaf is one of the diversity of toothpastes on the market. This study entitled The Effectiveness of Betel Leaf Herbal Toothpaste And Non-Herbal In Inhibiting Plaque Accumulation.The purpose of the study was to determine the effectiveness of betel leaf herbal toothpaste and non-herbal toothpaste in inhibiting plaque accumulation. This research was conducted using a literature study method. The results showed that betel leaf herbal toothpaste was effective in inhibiting plaque accumulation.The conclusion of this study is that betel leaf herbal toothpaste is effective in inhibiting plaque accumulation compared to non-herbal toothpaste.